Reclaiming the political in Latin American history : essays from the North - Joseph, G. M. (Gilbert Michael), 1947- (American encounters/global interactions., 2001)
A collection of essays and case studies on Latin America which suggest new historiographical approaches and political strategies, linking materialist analysis to constructivist understandings of power, meaning, identity, and agency.